Forced Marriage as Social Sanction: An Islamic Legal, Customary, and Human Rights Analysis in Rural Indonesia - Rosim, Moch.; Jannah, Shofiatul; Rodafi, Dzulfikar (Faculty of Sharia and Law, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
This research aims to analyze the practice of forced marriage in Batobella Village from the perspectives of Islamic law, custom, and human rights, with a focus on the principles of consent, social control mechanisms, and legal implications. This study examines the interaction between customary norms, religious law, and positive law with a focus on the principles of legitimacy, social dynamics, and opportunities for policy intervention that align with the maqāṣid al-sharīʿah. The research method employs a qualitative case study approach, utilizing data collection techniques that include in-depth interviews, participant observation, and document analysis. The informants consisted of traditional leaders, religious figures, victims, families, and youth. Data analysis was conducted thematically to identify patterns and relationships between variables, integrating comparative fiqh perspectives across schools of thot with field findings. Research in Batobella Village shows that forced marriage practices still persist as a mechanism for resolving violations of customary norms, with decisions often made unilaterally by families and traditional leaders without considering the bride's consent. Social pressure, stigma, and the threat of exclusion make it difficult for victims to refuse. Most marriages are not registered at the KUA, which weakens their legal protection. The role of religious figures is often compromised in favor of custom for the sake of social cohesion. Although some young people are starting to reject this practice, their views are still in the minority and are hindered by the dominant customary authority in marriage decisions.